STUDENT SCIENTIFIC GROUP WORK WITHIN THE SYSTEM OF PROFESSIONAL ADAPTATION IN UKRAINE - Trefanenko, Iryna; Soloviova, Olga; Hrechko, Svitlana (The scientific heritage (Budapest, Hungary), 2023)
The correct approach to organization of student’s self–learning process is of uppermost importance for suc- cessful higher education. Classroom work in higher education institutions aims at setting and giving direction functions of a teaching/learning process, and it is a student who is responsible for active knowledge acquisition through different means. Participating in different students’ societies and carrying out scientific re search work may become the most appropriate forms of active acquisition. Systematic work in students’ societies performing research independently as well as in close cooperation with scientific advisors satisfies two main criteria of social and psychological adaptation: satisfaction from independently obtained results of scientific research and social success, which presupposes conquering new life conditions and gaining respect from fellow students and teaching staff. The theoretical basis of the concept of adaptation is the idea of a continuous process of active adaptation of the individual to the environment that concerns all levels of human functioning. Participation in student scientific groups plays a major role in the student's socio–psychological adaptation. Results obtained in the course of our research proved that there was statistically valid difference in 6th–year students’ adaptation. It should be pointed out that the 6th–year is the time of the so–called “third crisis” of higher education. It appears due to the issue with work allocation and transition from studying to working lifestyle, also comparing possessed and desired knowledge and skills may bring a certain dissonance into student’s self– perception. Students consider the influ- ence of their profession on their future welfare. All these issues can be dealt with easier in case of students who have attended scientific societies and groups, who have tried their hands in practical aspects and improved their knowledge. The results of our analysis are the following. The purpose of the paper lies in comparing psychological and social adaptation of students who participate in scientific groups and are engaged in scientific research with that of students who refrain from such activities. Material and methods. To study social and psychological adap- tation 154 students were asked to fill in a questionnaire based on the K. Roger and R. Dimond’s methodology. Results and discussion. We find that the adaptation in the group of students engaged in the research activity is much higher. Thus, in the first group, the index of emotional comfort is 85%, while the second group has the index of 67%. Researches evaluated the statements about a person, about the way of professional life, experiences, thoughts, habits, behavioral styles on a six–point scale: Adaptation, Self–Perception, Perception of Others, Emo- tional Comfort, Internality, Domination. Considerable difference between control and experiment groups is estab- lished for internality, emotional comfort, and self–perception and perception of others. Conclusion. The obtained results proved that participation in scientific societies increased students’ ability for adaptation and helped to de- velop a socially and psychologically healthy professional with such grounded qualities as self–respect, self–un- derstanding, independence and assertiveness.
Теоретичною основою поняття «адаптація» є уявлення про неї як про постійний процес активного пристосування індивідуума до умов навколишнього середовища, який торкається всіх рівнів функціону- вання людини. Робота в студентській науковій групі, залучення студентів до виконання науково–дослідної роботи відіграє велику роль в соціально–психологічній адаптації студента. Метою нашої роботи стало по- рівняти соціально– психологічну адаптацію у студентів, які приймали активну участь в роботі гуртків та виконували науково–дослідні роботи під час навчання в університеті зі студентами, які не були залучені до цього виду роботи. В результати дослідження було виявлено, що адаптація у студентів обох груп більше 80%. Цей результат не наближений до 100%, тому що, незважаючи на 6 рік навчання в університеті, сту- денти мають ряд особливостей в цей період, які впливають на їх адаптаційний рівень. В 1–й групі ми от- римали цей показник незначно вищим на 7% за контрольну групу. Це можна пояснити тим, що відсоток студентів, які активно залучались до науково–дослідної роботи, визначились з подальшою спеціалізацією та вже працюють в тому напрямку. В дослідній групі адаптовані студенти частіше проявляють інтерналь- ність, сприймають всі зміни, що відбуваються з ними, як результат власної діяльності (входження в режим роботи, самостійне складання графіка навчання, здатність встигати додатково навчатися та виконувати науково–дослідну роботу). Лише 9% в цій групі студентів сприймають події, які відбуваються, як вплив інших сил (судьба, випадок та інше). У контрольній групі цей відсоток вищий в два рази, це може прояв- лятися в житті студента у вигляді порушення самоорганізації. Емоційна комфортність в групі студентів, які займаються НДР значно вища. Так в першій групі показник складає 85% [75,48–94,52] на відміну від другої групи 67% [60,53–73,47] (р≤0,05). Перевага позитивних емоцій, відчуття благополуччя пов’язана з визначенням подальшого напрямку навчання, отриманням, за рахунок науково–дослідної роботи в гурт- ках, перших професійних перемог, позитивною самореалізацією у вибраному напрямку. В контрольній групі більше 1/3 студентів переживає емоційний дискомфорт на цьому рівні навчання, що значно обтяжує процес навчання. Отриманні дані в контрольній групі свідчать про майже однаковий відсоток рівня са- мосприйняття та сприйняття інших. Студенти демонструють дружне відношення до своїх сокурсників, що свідчить про прийняття оточення, схвалення їх життєвої позиції, в цілому позитивного відношення до себе оточуючих. У студентів дослідної групи виявляється позитивний полюс самосприйняття, що відображає ступінь доброзичливості до себе та відображає здатність оцінювати свої сильні та слабкі сторони. Більш низький показник прагнення до домінування в групі студентів, які відвідували гурток обумовлений напевно більшою здатністю роботи в команді. Отже, ми бачимо, що студенти, які відвідують гуртки, до- датково виконують НДР більше використовують свої адаптаційні можливості.
Keywords: socio–psychological adaptation; student scientific circle